A Change to Improve Health Quality: Benefits of the Human Opportunity Index (HOI) - Eri Mardison (Program Studi Kesehatan Masyarakat Universitas Sari Mutiara Indonesia, 2020)
There are a number of faktors that cannot be chosen by a child, such as gender, place of residence, number of family members, sex of the head of the household, the work status of the head of the household, the education of the head of the household, and the income per capita of the head of the household. HOI shows the access of a child in West Sumatra in 2019 to basic needs such as safe water, proper sanitation, proper housing and electricity. Clean water has covered 79.67 percent, of which 7.14 percent of the opportunity needs to be allocated to ensure equality in 2019. Proper sanitation, coverage has been 61.04 percent with reallocation of opportunities to ensure equity in 2019 of 10.88 percent. Furthermore, houses worthy of new coverage are 47.02 percent and opportunities that need to be reallocated to ensure equality in 2019 are 16.73 percent. Meanwhile, access to electricity coverage has been very good, 98.74 percent and reallocation of opportunities is only 0.76 percent. The most influential faktors are the income per capita and the education of the head of the household. Thus increasing the coverage and equity of this problem will require not only direct government assistance interventions such as housing assistance but also campaigns on all necessary accesses. This is one of the benefits of this research in mapping the problems that occur and efforts to improve them.